Distribution, development, transformation characteristics, and hydrate prospect prediction of the rift basins of northwest Zealandia in the Southwest Pacific - Song, Lijun; Feng, Xuliang; Yang, Yushen; Li, Yamin (Frontiers in Earth Science, 2022)
As the last area with unknown oil exploration potential, Zealandia has attracted the attention of petroleum scientists. Under the constraint of the known rift distribution, the gravity and magnetic anomaly data are utilized to predict the distribution of rift basins, and the balanced cross-section technique and basin simulation technique are utilized to analyze the development of the rift basins and hydrocarbon generation history of source rocks for the hydrate prospect prediction of the rift basins of northwest Zealandia. The time of rifting in Zealandia varies greatly from place to place, and it has experienced extensive rifts, migrated to the east of the Lord Howe Ridge, migrated to the west of the Lord Howe Ridge, migrated to the west of the Dampier Ridge, and finally migrated to both sides of the Lord Howe Ridge and then experienced multiple stages of compression transformation and deep burial transformation. The Upper Cretaceous coal source rock in the rift Ⅱ stage has entered the wet gas generation stage in the deep part of the rift or deeper rift on the eastern side of the Lord Howe Ridge, and the coal-generated wet gas may migrate along the fault and form a gas hydrate in the shallow seabed stable zone.